SNOMED CT: a potential powerhouse in the health record revolution. Issue 9 (2nd September 2022) - Roberts, Luke; Lanes, Sadie; Cooper, Carolyn
Abstract : In this article, Roberts et al discuss the importance of SNOMED CT in improving electronic health records, and the benefits this can bring healthcare organisations, professionals and patients.